Antibacterial Activity of Kaffir Lime Leaf (Citrus hystrix DC) Ethanol Extract against Staphylococcus aureus and Escherichia coli - Azhar, Gustika; Ridwanto, Ridwanto; Nasution, Haris Munandar; Pulungan, Ainil Fithri; Rani, Zulmai (Pustaka Media Publishing, 2024)
The use of herbal medicine has been increasing, which encourages researchers to use herbal materials as an alternative antibacterial, one of which is the kaffir lime leaf plant. This study was to identify the group of secondary metabolite compounds and examine the antibacterial properties of ethanol extract of kaffir lime leaves (Citrus hystrix DC) against Staphylococcus aureus and Escherichia coli bacteria. This study began with the preparation of simplisia powder, extracting kaffir lime leaf with ethanol, and the antibacterial activity test of extracts. The results of the study showed that the secondary metabolites contained in kaffir lime leaves are alkaloids, flavonoids, saponins, tannins, steroids and glycosides. Antibacterial activity test on Staphylococcus aureus bacteria showed that the ethanol extract of kaffir lime leaves with the best concentration inhibited the bacterial inhibition zone at a concentration of 10% with an inhibition diameter of 22.21 mm with a very strong category dan the best concentration is 10% with an inhibition diameter of 20.48 mm with a very strong category for Escherichia coli bacteria. Ethanol extract of Kaffir Lime leaves has been proven to inhibit Staphylococcus aureus and Escherichia coli bacteria.